JEFF BEZOS THE WORLD-CHANGING ENTREPRENEUR - McNab, Chris (Arcturus Publishing Limited, 2023)
Jeff Bezos is the definition of the word 'magnate' - executive chairman of Amazon and the first centibillonaire on the Forbes' wealth index. Amazon, the online marketplace he imagined on a road trip between New York and Seattle in 1994, is now the largest online sales company and generates more money than any other company on the Internet. Later, Bezos founded an aerospace manufacturer, Blue Origin, that took a vehicle to space in 2015. He became the owner of the Washington Post in 2013. His wealth is currently estimated at more than $200 billion and is one of the top three wealthiest men on earth. This absorbing book looks at Bezos' particular abilities and what sustains his incredible drive to succeed.